Cochlear implantation in Malawi: report of the first four cases. Issue 10 (15th August 2017) - Mulwafu, W; Strachan, D R; Bartlett, R; Caron, C
Abstract: Objective: This paper reports on the first four cochlear implant cases in Malawi. Case reports: Three patients were deafened from infectious diseases and one from an unknown cause. They all had post-lingual deafness. Six months after the last implant, they are all progressing well. Conclusion: Despite significant practical difficulties, it has proved possible, with the right support, to carry out cochlear implantation in one of the world's poorest countries. The project has also raised awareness of deafness in Malawi and highlighted significant public health issues relating to the aetiology of deafness in developing countries.